Synthesis of a 3,7-Disubstituted Isothiazolo[4,3-b]pyridine as a Potential Inhibitor of Cyclin G-Associated Kinase - Tom Grisez; Nitha Panikkassery Ravi; Mathy Froeyen; Dominique Schols; Luc Van Meervelt; Steven De Jonghe; Wim Dehaen (Molecules, 2024)
Disubstituted isothiazolo[4,3-b]pyridines are known inhibitors of cyclin G-associated kinase. Since 3-substituted-7-aryl-isothiazolo[4,3-b]pyridines remain elusive, a strategy was established to prepare this chemotype, starting from 2,4-dichloro-3-nitropyridine. Selective C-4 arylation using ligand-free Suzuki-Miyaura coupling and palladium-catalyzed aminocarbonylation functioned as key steps in the synthesis. The 3-N-morpholinyl-7-(3,4-dimethoxyphenyl)-isothiazolo[4,3-b]pyridine was completely devoid of GAK affinity, in contrast to its 3,5- and 3,6-disubstituted congeners. Molecular modeling was applied to rationalize its inactivity as a GAK ligand.